2015
DOI: 10.1007/s11357-015-9816-7
|View full text |Cite
|
Sign up to set email alerts
|

Fatiguing exercise initiated later in life reduces incidence of fibrillation and improves sleep quality in Drosophila

Abstract: As the human body ages,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 56 publications
(49 reference statements)
0
44
0
Order By: Relevance
“…Finally, as is known, exercise training was good for lengthening health-span and reducing the risk of some diseases. In both humans and animals, numbers of studies have confirmed that moderate exercise improves the quality of life and prolongs lifespan [ 16 , 27 , 50 ]; however, obesity leads to a variety of diseases and a bad quality of life [ 4 , 5 ]. This phenomenon confirmed again in our research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, as is known, exercise training was good for lengthening health-span and reducing the risk of some diseases. In both humans and animals, numbers of studies have confirmed that moderate exercise improves the quality of life and prolongs lifespan [ 16 , 27 , 50 ]; however, obesity leads to a variety of diseases and a bad quality of life [ 4 , 5 ]. This phenomenon confirmed again in our research.…”
Section: Discussionmentioning
confidence: 99%
“…Most flies continued to respond by climbing throughout the exercise period. The few that failed to climb were actively walking at the inner wall of the vial [ 17 , 27 ]. Flies were exercised in vials with a 2.8-cm inner diameter, rotated at 0.18 rev/s, 0.20 rev/s, 0.18 rev/s, 0.16 rev/s, and 0.14 rev/s.…”
Section: Methodsmentioning
confidence: 99%
“…The few that failed to climb were actively walking on the inner wall of the vial. Based on the best exercise program that has been determined, we selected continuous exercise for 2.5 h (Zheng et al, 2015).…”
Section: Nh and Exercise Training Devices And Protocolsmentioning
confidence: 99%
“…Mild NH and modest exercise training can instill beneficial effects on the body. Our research team has explored optimal exercise and NH protocols (Zheng et al, 2015;Wang et al, 2017). The purpose of the present investigation was to study changes in cardiac structure and function and behaviors that include sleep-activity and negative geotaxis of aged flies induced by NH and exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Dropping the enclosures results in the animals being knocked to the bottom of the enclosure, and due to their negative geotaxis response, they will attempt to climb to the top of the enclosure until they are dropped again . The Power Tower is a relatively intense form of exercise, and to induce a more gentle form of exercise, other groups have used partial (Swing Boat) or full rotations (Treadwheel, Rotating Exercise Quantification System [REQS], system developed by the Key Laboratory of Physical Fitness and Exercise Rehabilitation of Hunan Province at Hunan Normal University in China) of the animal enclosures to induce exercise. When the animal enclosures are rotated, the orientation of “up” changes, and the animals are stimulated to continue to move, leading to exercise compared to control flies.…”
mentioning
confidence: 99%